Digital Komunikasi Untuk Kegiatan Organisasi Remaja Mesjid - Fitri Firdalius; Dinda Djesmedi; Wahyuni Fithratul Zalmi (Asosiasi Dosen Pengabdian kepada Masyarakat Indonesia, 2021)
Due to the current state of the COVID-19 pandemic, it is necessary to practice social distancing. The use of digital communication is needed, therefore we can use digital communication in mosque youth activities, especially the Jamiek Mosque Youth Organization. With this digital communication technology, we can communicate indirectly or face to face with someone or many people with whom we will communicate. The purpose of this paper is to provide information and implementation in the use of digital communication. Based on this goal, utilizing social media such as Whatsapp, Facebook, Instagram, Google Meet, and others to support the activities of mosque youth. The results show that digital communication can maximize mosque youth activities, facilitate long-distance communication, obtain remote information, reduce costs, and shorten time.